Constructing spin-structured focal fields for chiral-sensitive trapping with dielectric metalens - Li, Bingjie; Xin, Yujie; Guo, Xuyue; Fan, Xinhao; Liu, Sheng; Zhao, Jianlin; Li, Peng (Frontiers in Physics, 2022)
Engineering the chiral field is crucial for the flexible manipulation of chiral particles. Some complex optical setups for constructing spin-structured fields have been well developed to sort particles with opposite chiralities toward opposite transversal directions. In this work, we demonstrate the robust construction of a class of focal field that possesses laterally variant optical spin angular momentum by using monolayer dielectric metalens. By utilizing the simultaneous modulation capacity of phase and polarization of dielectric metalens, we can establish line focus with laterally tailored gradient optical helicity. The focusing property of this metalens and polarization structure of focal field are theoretically analyzed by a hybrid vector focusing model, and experimentally demonstrated by NA=0.2 and 0.5 samples. We illustrate that this type of gradient helicity offers opportunities to induce laterally chiral-sensitive force for chiral particle.